COVID-19 associated pulmonary aspergillosis (CAPA) in a pregnant woman - Shruti Agrawal; Ravi Hari Phulware (University of São Paulo, 2021)
Viral or bacterial co-infections with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been reported in the literature. However, the knowledge on Aspergillus co-infection among patients with coronavirus disease 2019 (COVID-19) is limited. COVID‐19‐associated pulmonary aspergillosis (CAPA) has been seen in critically ill COVID-19 patients with acute respiratory distress syndrome (ARDS), which has raised concerns about the worsening disease course of COVID-19 and increasing mortality. We describe a clinical case of CAPA infection and acute respiratory distress syndrome (ARDS) with a deathly outcome in a previously well, non-immunocompromised pregnant woman with intrauterine death of the fetus. Hence, we suggest that clinicians and pathologists keep alerting the possible occurrence of pulmonary aspergillosis in severe/critical COVID-19 patients, and aggressive investigations should be done to rule out the possibility of CAPA so that early treatment can be administrated.